Responsiveness and construct validity of two outcome measures of bilateral upper limb function in patients with chronic stroke - Tsai, Han-ting; Lau, Hiu-ying; Lin, Keh-chung; Li, Yi-chun; Lin, Chia-jung; Yao, Grace; Lee, Ya-yun; Chen, Wen-shiang; Chen, Chia-ling; Chang, Ya-ju; Horng, Yi-shiung (Frontiers in Neurology, 2024)
Background: Stroke is a leading cause of long-term disability among stroke survivors. Despite the availability of numerous stroke rehabilitative therapies, such as mirror therapy, bilateral arm training, and robot-assisted therapy, the recovery of motor function after stroke remains incomplete. Bilateral arm function is a key component in stroke patients to perform activities of daily living and to reflect their functional autonomy. Objective: This clinimetric study investigated and compared the construct validity and responsiveness of 2 bimanual activity outcome measures, the Chedoke Arm and Hand Activity Inventory (CAHAI) and the ABILHAND Questionnaire, in individuals receiving stroke rehabilitation. Methods: The present study is a secondary analysis following the framework of the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN). Individuals with chronic stroke (N = 113) were recruited from outpatient rehabilitation settings. Participants received 18 to 20 sessions of robot-assisted therapy, mirror therapy, combined therapy, or conventional rehabilitation for 4 to 6 weeks. The CAHAI, ABILHAND Questionnaire, and a comparison instrument, the Motor Activity Log (MAL), were administered twice at a 4- to 6-week interval to all participants. ABILHAND scores, in logits, were converted from raw ordinal scores into a linear measure. Results: There was medium to large correlation of the CAHAI and the MAL (ρ = 0.60-0.62, p < 0.01) as well as the ABILHAND Questionnaire and the MAL (ρ = 0.44-0.51, p < 0.01). Change scores from the initial measurement to the post-intervention measurement demonstrated small to medium correlation of the CAHAI and the MAL (ρ = 0.27-0.31, p < 0.01) and medium to large correlation of the ABILHAND Questionnaire and the MAL (ρ = 0.37-0.41, p < 0.01). Overall, 7 of 8 hypotheses were supported. The hypothesis testing regarding the construct validity and responsiveness of the CAHAI and ABILHAND Questionnaire was confirmed. Conclusions: The CAHAI and ABILHAND Questionnaire are both responsive and suitable to detect changes in bilateral arm functional daily activities in individuals with chronic stroke. Further study with a prospective study design to capture specific clinical features of participants and the use of body-worn sensors, such as the arm accelerometer, is suggested.